A conceptual framework for predicting flood area in Terengganu during monsoon season using association rules - Azwa, Abdul Aziz; Engku Fadzli Hasan, Syed Abdullah; Julaily Aida, Jusoh (Asian Research Publishing Network, 2016)
Over the last decade, flooding has been one of catastrophic disaster which causes economic damage, lost life and environmental deprivations. The need for flood prediction is rising since the decision maker lacks intelligent tools to predict flood areas. The data mining and geospatial visualization will test the temporal data which include river flow and rainfall data to find patterns and new information which then will use to predict areas that expose to flood. Since Terengganu situated at east peninsular, every year in October to March will be having heavy rainfall and increasing of sea levels. To this extent, we propose a framework to support flood prediction which the outcome will intention to better manage floods through prevention, protection and emergency response.